1986
DOI: 10.1002/j.1875-9114.1986.tb03473.x
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Low‐Dose Hydrochlorothiazide on Blood Pressure, Serum Potassium, and Lipoproteins

Abstract: Recent clinical trials in hypertension suggest that thiazide diuretics may increase coronary heart deaths in selected patients, possibly through adverse effects on serum potassium, lipids, lipoproteins, and/or apolipoproteins. Administration of smaller doses of diuretics has been recommended to decrease this risk. We evaluated 12.5-mg and 112.5-mg daily doses of hydrochlorothiazide (HCTZ) administered for 1 month to nine postmenopausal black female hypertensives using a double-blind, randomized, crossover desi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

1988
1988
2012
2012

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 47 publications
(9 citation statements)
references
References 31 publications
(1 reference statement)
0
9
0
Order By: Relevance
“…Losartan/HCTZ significantly reduced serum potassium level but to within normal ranges, which was also reported in the previous study. A low dose of HCTZ (12.5 mg/day) produced less hypokalemia than a dose of 25 mg/day or more ( 14 ). Diuretic-induced hypokalemia, potassium level < 3.5 mmol/ L, is known to cause an indirect reduction in insulin secretion leading to elevated serum glucose concentration ( 15 ).…”
Section: Discussionmentioning
confidence: 99%
“…Losartan/HCTZ significantly reduced serum potassium level but to within normal ranges, which was also reported in the previous study. A low dose of HCTZ (12.5 mg/day) produced less hypokalemia than a dose of 25 mg/day or more ( 14 ). Diuretic-induced hypokalemia, potassium level < 3.5 mmol/ L, is known to cause an indirect reduction in insulin secretion leading to elevated serum glucose concentration ( 15 ).…”
Section: Discussionmentioning
confidence: 99%
“…Diuretic-related reductions in serum K ϩ are typically dose related and usually range from 0.2 to 0.6 mmol/L. [11][12][13][14][37][38][39][40][41] This well-described relationship is depicted by arrow "A" in Figure 1. A recent meta-analysis of 59 studies involving 83 thiazide diuretic treatment arms found a significant correlation between the degree of diuretic-induced hypokalemia and the increase in plasma glucose, and there was evidence that prevention of hypokalemia with K ϩ supplementation or potassium-sparing agents lessened the degree to which plasma glucose increased consequent to diuretic therapy.…”
Section: Possible Relationship To Hypokalemiamentioning
confidence: 99%
“…Another study found reductions in SBP of 29, 21, 32, and 24 mm Hg in 51 elderly patients randomly assigned to 25 mg daily, 25 mg twice daily, 50 mg daily, and 50 mg twice daily, respectively. 55 Five important principles are evident with HCTZ dosing: (1) some patients will respond to doses of 12.5 mg daily, (2) doses Ͼ25 mg daily often lower BP only slightly more than does 25 mg (ie, a relatively flat dose response), (3) hypokalemia is dose related, and the risk increases with dose, 53,57,58 (4) there is a great deal of variability in response with some patients, requiring doses of 25 to 50 mg before substantial antihypertensive effects are observed, 22,52,53 and the reduction in BP is greater when baseline BP is highest.…”
Section: Dose Responsementioning
confidence: 99%